2011
DOI: 10.1097/mca.0b013e3283472a71
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin levels in acute myocardial infarction and stable coronary artery disease

Abstract: The plasma level of NGAL is higher in patients with AMI compared with the patients with stable CAD. This finding may suggest an active pathophysiological role for NGAL in development of acute coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 27 publications
2
30
0
4
Order By: Relevance
“…It may also exist in a urinary dimeric form secreted by activated leukocytes in the setting of urinary tract infection [11]. Blood NGAL has been found to be elevated the setting of acute myocardial infarction to a greater extent than in patients with stable coronary artery disease [12,13]. We believe blood levels >200 ng/ml observed in our study reflect abnormal production of NGAL in the basal and post-contrast state.…”
Section: Discussionmentioning
confidence: 53%
“…It may also exist in a urinary dimeric form secreted by activated leukocytes in the setting of urinary tract infection [11]. Blood NGAL has been found to be elevated the setting of acute myocardial infarction to a greater extent than in patients with stable coronary artery disease [12,13]. We believe blood levels >200 ng/ml observed in our study reflect abnormal production of NGAL in the basal and post-contrast state.…”
Section: Discussionmentioning
confidence: 53%
“…In a recent study, increased NGAL levels were found to be an independent predictor of death and major adverse cardiac event outcomes in patients who received primary percutaneous coronary intervention for ST segment elevation myocardial infarction [26]. In addition, serum NGAL levels were found to be a useful predictor of the presence of CAD [32]. In this study, we describe for the first time the correlation of NGAL levels in patients with noncritical lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly in another study, serum NGAL levels showed an increasing tendency in CAD and AMI, although this was not significant. In the study by Arslan et al (38) that compared patients with stable CAD and AMI, significantly higher plasma NGAL Neutrophil Gelatinase-Associated Lipocalin and Pentraxin 3 in Acute Coronary Syndrome levels were detected in the AMI group; however, no difference was found between STEMI and NSTEMI. It was concluded that NGAL NGAL levels are more successful indicator in detecting MI than other inflammatory markers.…”
Section: Discussionmentioning
confidence: 97%